2015
DOI: 10.19173/irrodl.v16i3.2015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring intensive longitudinal measures of student engagement in blended learning

Abstract: In this exploratory study we used an intensive longitudinal approach to measure student engagement in a blended educational technology course, collecting both self-report and observational data. The self-report measure included a simple survey of Likert-scale and openended questions given repeatedly during the semester. Observational data were student activity data extracted from the learning management system. We explored how engagement varied over time, both at the course level and between students, to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 48 publications
1
82
0
2
Order By: Relevance
“…The rest of the elements are showing the value of κ approaching the value of 1 which means the assessor reaches the consent of the assessors. This finding in line with the result from Henrie et al, (2015) where they stated that blended learning need to be apply in learning process to make sure students will engaged in class activity. Findings from Zacharis (2015), Okaz (2015) (2016) also showed that the multivariate elements in learning helps student to get involved in classroom activities, especially by using social media technologies.…”
Section: Findings and Discussionsupporting
confidence: 83%
“…The rest of the elements are showing the value of κ approaching the value of 1 which means the assessor reaches the consent of the assessors. This finding in line with the result from Henrie et al, (2015) where they stated that blended learning need to be apply in learning process to make sure students will engaged in class activity. Findings from Zacharis (2015), Okaz (2015) (2016) also showed that the multivariate elements in learning helps student to get involved in classroom activities, especially by using social media technologies.…”
Section: Findings and Discussionsupporting
confidence: 83%
“…As noted by Alhazmi and Rahman (2014), it is important to bear in mind that social networking sites by themselves cannot explain student commitment. Furthermore, as indicated by Henrie, Bodily, Manwaring, and Graham (2015), in order to analyse continuing student participation, it is necessary to consider variables such as the clarity of instruction and the relevance of the proposed activities. It is possible that the proposed Twitter activity on the courses analysed lacked relevance, which could explain this lack of commitment to and participation on social media.…”
Section: Discussionmentioning
confidence: 99%
“…By themselves, networks alone do not reinforce student commitment; instead, this may be influenced by a multitude of factors (Alhazmi & Rahman, 2014). As Henrie, Bodily, Manwaring, and Graham (2015) have indicated, in an analysis of continued student participation over time in virtual learning settings, it is important to bear in mind that the clarity of the instruction and the relevance of the activities exert more influence on student satisfaction than the medium used for instruction. Forbes (2017) has highlighted the importance in social media-based teaching of offering different types of support according to the students' experience and confidence with social media platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies conducted on both online student module data and online student module engagement employ mainly quantitative approaches such as surveys and quantitative metrics (e.g., login data and grades) as part of their overall methodology (see, for instance, Bahati, Fors, & Tedre, 2017;Dixson, 2015;Henrie, Bodily, et al, 2015;Henrie et al, 2018;McGarrigle, 2013;Vogt, 2016). For example, Henrie, Bodily, et al's (2015) review study of 113 student engagement studies reports that 39.8% of these studies used qualitative measures.…”
Section: Methodsmentioning
confidence: 99%